Answer:
1) y = 12
2) x = 4
3) w = -3
4) k = -35
Step-by-step explanation:
If that helps, but I'm pretty sure the answer is -1 that is what I have found in Google that is what all the answers are that in finding.
Answer:
1. 2(k + 3)
2. 3. 75 + k
Step-by-step explanation:
1. 2x + 6
Since, 2 is a common factor of 2 and 6, we can take that common outside.
So, 2x + 6 = 2(x + 3)
Note that in the initial expression, this 2 was distributed to arrive at 2x + 6.
2. (1.5 + k) + 2.25
This is simple addition. We can simply remove the brackets to have:
1.5 + k + 2.25
Since, the like terms can be added, we will have:
1.5 + 2. 25 + k
= 3. 75 + k
6(2k-3) is the answer to this problem.
make a distributive
take the 6 out of the equation and u have remaining 2k-3. 6(2k-3)